1979
DOI: 10.1111/j.1365-2621.1979.tb03470.x
|View full text |Cite
|
Sign up to set email alerts
|

Corn Protein Concentrate: Functional and Nutritional Properties

Abstract: The functional and nutritional properties of a bland, light colored corn protein concentrate (MCPC) have been investigated. This material contains 67% protein (dsb) and less than 0.5% fat. The water solubility is low, but water and fat binding properties are similar to those of a commercial soy concentrate. MCPC is rich in methionine and cystine, and forms complementary protein mixtures having enhanced nutritive value with soy products. The PER of a 20/80 (protein basis) mixture of MCPC and soy concentrate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 16 publications
2
22
2
1
Order By: Relevance
“…The amount of water present in processed products will depend on the extent to which the dry ingredients absorb or adsorb water under various environmental conditions. [32] Nielsen et al [25] reported water-binding capacity of 420−690% for corn germ meal, which are significantly higher than those observed in the present study. Maize germ protein flour rich in starch has also been reported to stabilize emulsions by absorbing or binding excess water, enabling more water to be added.…”
Section: Physical and Functional Properties Flour Blendscontrasting
confidence: 89%
“…The amount of water present in processed products will depend on the extent to which the dry ingredients absorb or adsorb water under various environmental conditions. [32] Nielsen et al [25] reported water-binding capacity of 420−690% for corn germ meal, which are significantly higher than those observed in the present study. Maize germ protein flour rich in starch has also been reported to stabilize emulsions by absorbing or binding excess water, enabling more water to be added.…”
Section: Physical and Functional Properties Flour Blendscontrasting
confidence: 89%
“…Composition and digestibility of CGPI and defatted corn germ (Table 1) were comparable to values reported in other studies: 17.8-22.0% protein, 0.3-1.5% fat, 5.4-9.2% ash, 75% digestibility for the defatted germ (Nielsen et al, 1973;Lucisano et al, 1984); 73% protein, 4.3% ash, and negligible fat in CGPI (Nielsen et al, 1973) and 82% digestibility for corn gluten protein concentrate (Phillips and Sternberg, 1979). The amino acid profile of CGPI was superior to defatted corn germ and exceeded most of the NRC Recommended Dietary Allowances (1980) essential amino acid requirements, including lysine (Table 1).…”
Section: Composition and Yieldsupporting
confidence: 88%
“…Colour is the first impression to register for utilisation of high protein materials in food products 24. Hunter colour values ( L , a , b and Δ E ) of the flours are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%